Programme evaluation and spillover effects. Issue 1 (2nd January 2016) - Angelucci, M.; Di Maro, V.
Abstract : This paper is a practical guide for researchers and practitioners who want to understand spillover effects in programme evaluation. It defines spillover effects and discusses why it is important to measure them. It explains how to design a field experiment to measure the average effects of the treatment on subjects, both eligible and ineligible, for the programme in the presence of spillover effects. In addition, it discusses the use of nonexperimental methods for estimating spillover effects when the experimental design is not a viable option. Evaluations that account for spillover effects should be designed such that they explain both the cause of these effects and whom they affect. Such an evaluation design is necessary to avoid inappropriate policy recommendations and neglecting important mechanisms through which the programme operates.